2017
DOI: 10.15406/joentr.2017.08.00261
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Benign Paroxysmal Positional Vertigo in a Case of Acoustic Neuroma

Abstract: We present the case of a patient with episodes of dizziness triggered by postural changes, with findings atypical to neurotological examination, and whose final diagnosis was an acoustic neuroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Furthermore, if the geotropic direction-changing PPN has been attributed to a floccular lesion [ 15 , 16 ], our patient presented with a tumor protruding in the PCA and previous surgery results in that area, so a clear central component on the PPN is possible. Carmona et al [ 17 ] also described another case of AN with short-latency geotropic PPN and no response to liberatory maneuvers. A case similar to our other case, with apogeotropic-type horizontal direction-changing PPN, is described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, if the geotropic direction-changing PPN has been attributed to a floccular lesion [ 15 , 16 ], our patient presented with a tumor protruding in the PCA and previous surgery results in that area, so a clear central component on the PPN is possible. Carmona et al [ 17 ] also described another case of AN with short-latency geotropic PPN and no response to liberatory maneuvers. A case similar to our other case, with apogeotropic-type horizontal direction-changing PPN, is described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's answer to the maneuvers applied was inconsistent and during the evolution she presented a vertical downbeat nistagmus which cannot be explained as due to changes related to severity. Carmona et al recently presented a 4 [4], where they found a prolonged geotropic horizontal nystagmus accentuated to the side in which the patient had an acoustic neuroma and the authors speculate that, given the size of the tumor, there may be a dynamic compression of the vestibular nuclei which may generate variable information on the velocity storage mechanism or perhaps a true BPPV with an impaired velocity storage mechanism [5]. The presence of atypical BPPV must be studied with imaging studies, in this case of acoustic neuroma, hearing was symmetric and the only key were the atypical signs of the BPPV as explained.…”
Section: Discussionmentioning
confidence: 99%
“…As we go down the ladder, we find less frequent forms which may overlap with positional vertigo of central causes. In recent years, many cases and series of cases have been published [12][13][14] o patients with a clinical picture of positional vertigo, who were initially diagnosed as BPPV but whose final diagnosis was of CPPV or vestibular neuritis; these cases match what is represented in the ladder.…”
Section: Atypical Positional (Apv)mentioning
confidence: 99%
“…Based on the findings of the aforementioned papers, we propose the following elements for a positional vertigo to be considered atypical: APV based on epidemiology: pediatric age, except post-HT [ 14 , 16 ]; APV based on direction of the nystagmus: purely torsional (purely vertical) change in the direction of the nystagmus [ 5 ]; APV based on duration: no latency, excessive duration [ 6 , 7 ]; APV based on therapeutic test: lack of response to maneuvers [ 5 , 6 , 7 , 12 , 13 , 14 ]; APV based on evolution: persistence of signs throughout time [ 5 , 6 , 7 , 13 ]. …”
Section: Atypical Positional (Apv)mentioning
confidence: 99%
See 1 more Smart Citation